2014
DOI: 10.1111/cbdd.12426
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Screening, and Molecular Docking Studies of Piperazine‐Derived Constrained Inhibitors of DPP‐IV for the Treatment of Type 2 Diabetes

Abstract: Novel piperazine-derived conformationally constrained compounds were designed, synthesized, and evaluated for in vitro Dipeptidyl peptidase-IV (DPP-IV) inhibitory activities. From a library of compounds synthesized, 1-(2-(4-(7-Chloro-4-quinolyl)piperazin-1-yl)acetyl)pyrrolidine (2g) was identified as a potential DPP-IV inhibitor exhibiting better inhibitory activity than P32/98, reference inhibitor. The in vivo studies carried out in STZ and db/db mice models indicated that the compound 2g showed moderate anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The inhibition of DPP-IV prevents the inactivation of gastric inhibitory polypeptide and glucagon-like peptide-1. Activation of GLP-1 and GIP can stimulate insulin secretion, which results in lowering of glucose levels and improvement of the glycemic control (Kushwaha et al 2015). Insulin sensitivity to cells is attributed to phosphorylation of the insulin receptor, protein tyrosine phosphatase 1B, which dephosphorylates the tyrosine residues of IR proteins, is primarily responsible for insulin resistance in T2DM (Jung et al 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The inhibition of DPP-IV prevents the inactivation of gastric inhibitory polypeptide and glucagon-like peptide-1. Activation of GLP-1 and GIP can stimulate insulin secretion, which results in lowering of glucose levels and improvement of the glycemic control (Kushwaha et al 2015). Insulin sensitivity to cells is attributed to phosphorylation of the insulin receptor, protein tyrosine phosphatase 1B, which dephosphorylates the tyrosine residues of IR proteins, is primarily responsible for insulin resistance in T2DM (Jung et al 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In order to overcome the short half-life of GLP-1 in the bloodstream, studies have mainly focused on identifying and developing DPP-IV inhibitors [ 20 , 21 ], modifying the structure of GLP-1, or searching for structural analogues that are more resistant to DPPIV cleavage [ 22 ]. Based on these studies, and the functional form of native GLP-1(7–36), a modified human GLP-1 (mGLP-1) was designed and constructed by site-specific mutations that would have resistance to both DPP-IV and trypsin cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…These data showed that G. bicolor bioactive compounds have comparable free-binding energy as observed for gliptin drugs. Gliptin drugs have been widely used as a positive control for DPPIV inhibitory experiments [ 10 , 62 ]. Among the gliptin drugs, anagliptin is believed to have the best half-maximal inhibitory concentration (IC 50 ) values when compared with sitagliptin and alogliptin [ 63 ].…”
Section: Discussionmentioning
confidence: 99%